The roles of social norms and leadership in health communication in the context of COVID-19 - Akfırat, Serap; Bayrak, Fatih; Üzümçeker, Emir; Ergiyen, Tolga; Yurtbakan, Taylan; Uysal, Mete Sefa (Elsevier Ltd, 2023)
The global struggle with the COVID-19 pandemic has lasted for almost three years. Although national and local leaders have often called on the public to comply with preventive measures through health communication, large sections of society sometimes violated precautions and did not adequately follow these calls. We propose that social norms and leaders' identity entrepreneurship characteristics could be essential in effective health communication. In line with this notion, we investigated the effects of social norm types and leadership on complying with preventive measures, the intention to be vaccinated, and prosocial behavioral tendency through a high-powered experiment that focused on three factors: leadership quality (presence/lack of entrepreneurship), descriptive norm (supportive/obstructive), and injunctive norm (supportive/obstructive). Results showed that when support for injunctive and descriptive norms was present, people tended to more readily adhere to preventive measures, get vaccinated, and engage in prosocial behavior. There was also a significant effect of the interaction between descriptive and injunctive norms on compliance with preventive measures. The compliance level was highest when both norm types were supportive and lowest when both were obstructive. The effect decreased in the discrepant norms condition, where one type of norm was supportive and the other obstructive. There is also a significant interaction between leadership and the descriptive norm, indicating that a combination of an entrepreneur leader and a supportive descriptive norm increases compliance with the preventive measure. We discussed the role of leadership and social norms in effective health communication.
Keywords: COVID-19; Health Communication; Leadership; Preventive Measures; Social Norms